(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article examines the issues of increasing efficiency through the integration of modern digital technologies into the activities of organizations. A private higher education institution was selected as the object of research, and the opportunities, problems and levels of impact of using electronic business platforms were analyzed in it. A survey was conducted to identify ways to improve the organization’s management, marketing, information exchange and educational processes through the introduction of electronic services and digital solutions. It covered aspects such as the state of electronic infrastructure, human resource readiness, the effectiveness of digital marketing and user satisfaction with services. The research results show that electronic business models are an important tool for effectively managing the organization’s activities and increasing competitiveness. Practical recommendations have been developed for the phased introduction of digital solutions in higher education institutions.